Study of analgesic activity of ethanol extract of Phlogacanthus thyrsiflorus on experimental animal models - Apurba Mukherjee, Meghali Chaliha and Swarnamoni Das (Bangladesh Pharmacological Society, 2009)
The aim of the study was to evaluate the central and peripheral analgesic action of Phlogacanthus thyrsiflorus in experimental animal models. The extract was prepared by percolation method and acute oral toxicity testing was performed as per OECD guidelines. Analgesic activity was assessed by tail flick method (for central action) and glacial acetic acid-induced writhing test (for peripheral action). Leaves extract (500 mg/kg, p.o.) and aspirin (100 mg/kg) showed significant peripheral analgesic activity (p<0.05). Leaves extract (500 mg/kg, p.o.) and pethidine (50 mg/kg, i.p.) also showed significant central analgesic activity (p<0.05). Naloxone (1 mg/kg, s.c.) was used to find the mechanism of central analgesic action. Some partial agonistic activity for the opioid receptors seems to be probable mechanism of action.